Cultural Factors and the Role of Privacy Concerns in Acceptance of Government Surveillance - Thompson, Nik; McGill, tanya; Bunn, anna; Alexander, rukshan (2020)
Though there is a tension between citizens’ privacy concerns and their acceptance of government surveillance, there is little systematic research in this space, and less still in a cross cultural context. We address the research gap by modeling the factors that drive public acceptance of government surveillance, and by exploring the influence of national culture. The research involved an online survey of 242 Australian and Sri Lankan residents. Data was analyzed using PLS, revealing that privacy concerns around initial collection of citizens’ data influenced levels of acceptance of surveillance in Australia but not Sri Lanka, whereas concerns about secondary use of data did not influence levels of acceptance in either country. These findings suggest that respondents conflate surveillance with the collection of data and may not consider subsequent secondary use. We also investigate cultural differences, finding that societal collectivism and power distance significantly affect the strength of the relationships between privacy concerns and acceptance of surveillance, on the one hand, and adoption of privacy protections, on the other. Our research also considers the role of trust in government, and perceived need for surveillance. Findings are discussed with their implications for theory and practice.